2017
DOI: 10.3892/mmr.2017.7953
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline exerts anti-inflammatory effects on cerebral ischemia reperfusion‑induced injury in a rat model via the p38 mitogen-activated protein kinase signaling pathway

Abstract: Pentoxifylline exhibits complex functions with extensive pharmacological effects and is used therapeutically due to its therapeutic effects and rapid metabolism in the body, with no cumulative effects and few side effects. The present study investigated the effects of pentoxifylline on cerebral ischemia reperfusion‑induced injury (IRI) through suppression of inflammation in rats. Hematoxylin and eosin staining was performed to evaluate the number of neurocytes, and ELISAs were applied to measure tumor necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…numerous studies have demonstrated that the neurological damage that occurs during cerebral i/r injury may be enhanced under various complex pathophysiological conditions such as inflammation and apoptosis, which subsequently regulates the cell death-related signaling pathway (2,20). Previous studies have revealed that excessive inflammation and neuronal apoptosis were critical factors for cerebral I/R injury (2,3,21).…”
Section: Discussionmentioning
confidence: 99%
“…numerous studies have demonstrated that the neurological damage that occurs during cerebral i/r injury may be enhanced under various complex pathophysiological conditions such as inflammation and apoptosis, which subsequently regulates the cell death-related signaling pathway (2,20). Previous studies have revealed that excessive inflammation and neuronal apoptosis were critical factors for cerebral I/R injury (2,3,21).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor α ( Dong et al, 2017 ), Caspases 3 and Bax ( Chaitanya and Babu, 2008 ), Nitric oxide synthase ( Chen et al, 2017 ), Interleukin 6 ( Aref et al, 2020 ), Glutamate receptors ( Sun et al, 2019 ) and Acid sensing ion channel ( Dibas et al, 2018 ) activation involved in disease progression. The virtual screening was performed by using PyRx virtual screening tool between Gallic acid and above cerebrotoxic proteins which are involved in cerebral stroke they are like Bax (PDB ID: 5 W60), Tumor necrosis factor α (PDB ID : 5UUI), Caspases 3 (PDB ID : 2DKO), Interleukin (PDB ID : 1ALU), Nitric oxide synthase (PDB ID : 6CIC) compared to standard drugs such as Minocycline (Pub Chem Id : 54675783), Quercetin (Pub Chem Id:5280343) with Acid sensing ion channel (PDB ID : 3S3X); Memantine (Pub Chem Id: 4054) with Glutamate receptor (Pub Chem Id:5ZG2).…”
Section: Methodsmentioning
confidence: 99%
“…Pentoxifylline constitutes a beneficial medication for ARDS and respiratory failure 12,13 . Research suggests the efficacy of pentoxifylline in improving end organ damage involving the heart, 14 the kidney, 15 the liver 16 and the brain 17 . Pentoxifylline helps more effectively control sepsis and lower its mortality in adults and neonates 18,19 …”
Section: Resultsmentioning
confidence: 99%